Os paradoxos do assimilacionismo: "usos e costumes" do colonialismo português em Moçambique - Macagno, Lorenzo Gustavo (1996)
The purpose of this dissertation is to isolate the principles that guided the portugues colonialism in Mozambique and attempts to describe and explain the logic operated by these principles. The subject focus is the portuguese colonialism as a whole, as a cultural system that implies practices and representations. This system has limits and internal stresses that operates in a "double device" in which the evidence – assimilation – exists side by side with the implicit but active – segregation.